Improving student’s biological literacy skills using ARVi learning media - Indriani, Risda Putri; Kurniati, Tri Handayani; Ristanto, Rizhal Hendi (Biosfer: Jurnal Pendidikan Biologi, 2024)
Biological literacy is crucial for students to consider solutions to problems after analyzing them from various perspectives. The purpose of this research is to enhance biological literacy by using ARVi (Augmented Reality Virus) learning media. The research type is a quasi-experiment using a control group pretest-posttest design. The research instrument is a multiple-choice test validated by experts and empirical validation. The expert validation result shows an average score of 3.8, which can be interpreted as the test instrument being valid and suitable for use as a biological literacy measurement tool. The empirical validation result indicates that 3 questions are invalid, while 17 questions are valid as a biological literacy measurement tool. The reliability test result shows that the biological literacy test instrument has a reliability coefficient of 0.835, which can be interpreted as 70% confidence that the instrument can be trusted. The data analysis result shows that the data is normally distributed and not homogeneous. The independent t-test result is a t-statistic of 3.16 with a t-table of 1.98 at an α=0.05. This indicates that there is an increase in results between the control group to experimental group. The paired t-test result is a t-statistic of 15.7 with a t-table of 0.68 at an α=0.05. This indicates that there is an increase in posttest results compared to pretest results. This indicates that the ARVi media can enhance all aspects of biological literacy. The highest increase in biological literacy occurs in the nominal (82%), multidimensional (64%), structural (52%), and functional (32%).